Global, regional, and national burden of myelodysplastic syndromes and myeloproliferative neoplasms, 1990-2021: an analysis from the global burden of disease study 2021 - Gou, Xinyue; Chen, Zhuo; Shangguan, Yudi (Frontiers in Oncology, 2025)
ObjectiveTo analyze the trends and cross-country inequalities in the burden of Myelodysplastic syndromes (MDS) and myeloproliferative neoplasms (MPN) over the past 30 years and forecast potential changes through 2045.MethodsEstimates and 95% uncertainty intervals (UIs) for incidence, deaths, and disability-adjusted life-years (DALYs) associated with MDS/MPN were obtained from the Global Burden of Diseases (GBD) 2021 database. We described the epidemiology of MDS/MPN at global, regional, and national levels, analyzed trends in the burden of MDS/MPN from 1990 to 2021 through overall, local, and multidimensional perspectives, decomposed the burden based on population size, age structure, and epidemiological changes, quantified cross-country inequalities in MDS/MPN burden using standard health equity methods recommended by the WHO, and predicted changes of MDS/MPN burden to 2045.ResultsThe global incidence of MDS/MPN has shown a marked increase, escalating from 171,132 cases in 1990 to 341,017 cases in 2021. Additionally, the burden was found to be significantly greater in men compared to women. The overall global burden of MDS/MPN exhibited a consistent increase from 1990 to 2021, although the growth rate showed a noticeable slowdown between 2018 and 2021. Decomposition analysis identified population growth as a key factor influencing the variations in the burden of MDS/MPN. An inequality analysis across countries indicated that high Socio-demographic Index (SDI) countries bore a disproportionate share of the MDS/MPN burden, with significant SDI-related disparities remaining evident. Interestingly, while the incidence and deaths of MDS/MPN, along with the age-standardized rate (ASR) for DALYs, are projected to decline annually from 2020 to 2045, the absolute number of cases for these indicators is expected to continue rising. By 2045, the projected numbers are estimated to reach 457,320 cases for incidence, 82,047 cases for deaths, and 1,689,518 cases for DALYs.ConclusionsAs a major public health issue, the global burden of MDS/MPN showed an overall increasing trend from 1990 to 2021, which was primarily driven by population growth and aging. The largest share of the MDS/MPN burden was seen primarily in men, with older demographics. Countries with elevated SDI experienced a significantly higher burden of MDS/MPN. While the burden of MDS/MPN was most pronounced in high SDI quintile, the fastest growth was observed in the low-middle SDI quintile, especially in tropical Latin America. This study highlighted great challenges in the control and management of MDS/MPN, including both growing case number and distributive inequalities worldwide. These findings provide valuable insights for developing more effective public health policies and optimizing the allocation of medical resources.